EFEKTIFITAS HAND MASSAGE TERHADAP SKALA NYERI PADA PASIEN POST OPERASI LAPARATOMI DI RS. DR. REKSODIWIRYO PADANG - Weny Amelia; Dita Melia Ananda Saputri (STIKes Buleleng, 2020)
Abstract Laparatomy is one of the major surgical procedures by making cuts on the lining of the abdominal wall that are experiencing problems (hemorrhage, perforation, cancer and obstruction). Laparatomy causes discomfort and trauma for patients, one of which is often complained of patients is pain. One technique to reduce pain intensity is the hand massage technique. The purpose of this study was to determine the effectiveness of hand massage on the scale of postoperative Laparatomi pain in Dr. Reksodiwiryo Hospital, Padang. The design of this study was quasi experimental design with pre and post test without control. Data was collected in May 2019 at RST Dr. Reksodiwiryo Padang. Purposive sampling technique, the number of samples is 10 respondents. The results showed the average pain scale of the patient before hand massage was 4.70 and the average pain scale after hand massage was 3.90. There was an effectiveness of hand massage on the scale of post-operative pain Laparatomi in RST Dr.Reksodiwiryo Padang (p = 0.003). From the results of this study there are differences in the scale of post-operative pain Laparatomi before and after a hand massage at Dr. Reksodiwiryo Hospital Padang (p = 0.003). Research can be an input for nurses to be able to apply to postoperative Laparatomi patients so that it can reduce pain levels and also be applied as a nursing intervention to reduce pain in postoperative Laparatomi patients. Keywords: Hand massage, laparatomy, pain